Mental health stigma and barriers to care in World Trade Center responders: Results from a large, population‐based health monitoring cohort. Issue 3 (25th November 2020) - DePierro, Jonathan; Lowe, Sandra M.; Haugen, Peter T.; Cancelmo, Leo; Schaffer, Jamie; Schechter, Clyde B.; Dasaro, Christopher R.; Todd, Andrew C.; Crane, Michael; Luft, Benjamin J.; Moline, Jacqueline M.; Harrison, Denise; et al.
Abstract: Background: Nearly 20 years after the terrorist attacks of September 11, 2001, multiple studies have documented the adverse mental consequences among World Trade Center (WTC) rescue, recovery, and clean‐up workers. However, scarce research has examined mental health stigma and barriers to care in WTC‐exposed individuals, and no known study has examined whether rates of endorsement may differ between police and "nontraditional" responders, the latter comprising a heterogeneous group of workers and volunteers. Objective: To identify the prevalence and correlates of mental health stigma and barriers to care in WTC responders. Methods: Mental health stigma and barriers to care and their correlates were examined in 6, 777 police and 6, 272 nontraditional WTC responders. Results: Nontraditional responders endorsed more stigma or barriers to care concerns than police responders. Within a subsample who screened positive for a psychiatric disorder, police were more likely than nontraditional responders to endorse "concerns that negative job consequences might result" (17.9% vs. 9.1%), while nontraditional responders were more likely to endorse "I don't know where to go to find counseling services" (18.4% vs.6.6%). Within this subsample, mental health service need and more severe WTC‐related posttraumatic stress disorder symptoms were associated with increased likelihood of endorsing stigma or barriers; pre‐9/11 psychiatric history and non‐Hispanic Black race/ethnicity were associated with lower likelihood of endorsing stigma or barriers. Conclusions: Results of this study underscore the burden of mental health stigma and barriers to care in WTC responders, and highlight the need for targeted interventions to address these concerns and promote mental healthcare utilization in this population.